Studi Kelayakan Produk Sabun Batang Berbahan Dasar Minyak Jelantah dengan Media Bantu Ecoenzyme - Seri Megawati; Adi Nugroho (AGROINTEK, 2021)
Cooking oil and ecoenzyme are one type of combination that can be used for making hand washing soap. The purpose of this study is to make soap from used cooking oil and ecoenzyme as the basic ingredients and see its compatibility with SNI standards. The process of making soap begins with the design of three different types of oil and ecoenzyme content formulations. There are three comparisons of oil and ecoenzyme content used, namely: F1 (66% and 11%), F2 (56% and 16%), F3 (46% and 21%). The parameters that become the benchmark in testing soap quality come from SNI 3532: 2016 and the Domestic Waste Quality Standards. Although the three types of formulas do not meet the overall SNI quality standards and Domestic Waste Quality Standards, the results of laboratory tests show that the third formula is the closest to SNI quality standards. Based on the results of statistical tests with multiple linear regression test models show that the oil content and ecoenzyme affect the increase in total fat in soap